Reactivity of the [η2-bis(tert-butylsulfonyl)acetylene](carbonyl)(η5-cyclopentadienyl)cobalt complex towards electron-rich and -poor ccetylenes - Goswami, Avijit; Stäb, Tobias; Rominger, Frank; Gleiter, Rolf; Siebert, Walter (European journal of inorganic chemistry, 2005)
The electron-rich aminoacetylenes Et2NC2R (2a-c, R = SPh, PPh2, and Ph, respectively) react smoothly with [η2-bis(tert-butylsulfonyl)acetylene](carbonyl)(η5-cyclopentadienyl)co-balt (1) to form the donor-acceptor stabilized (η4-cyclobutadiene)cobalt complexes 3a-c in good yields. However, treatment of the electron-poor borylacetylenes 2d-f with the cobalt complex 1 does not lead to the expected (η4-cyclobutadiene)cobalt complexes. Analogously, the reaction of bis(1-phenylethynyl)sulfide (2g) with two equivalents of 1 gives rise to the sulfur-bridged bis[η4-(cyclobutadiene)cobalt] complex 3g. The new cobalt complexes were characterized by NMR spectroscopy, mass spectrometry, and by X-ray structure analysis for 3a, which reveals almost equal C-C bond lengths within the cyclobutadiene ring. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005)
Dedicated to Prof. Günter Helmchen on the occasion of his 65th birthday
Im Titel erscheinen die Ziffern 2 und 5 hochgestellt
Gesehen am 23.10.2020
Keywords: Festschrift